REFLECTION ON LEGAL STUDIES OF BENEFICIAL OWNERS IN CORPORATIONS COMMITTING MONEY LAUNDERING AND TERRORISM CRIMES IN INDONESIA - Refans Jaka Pratama Yudha; Benny Djaja (LPPM Universitas Ekasakti Padang, 2023)
In order to advance and develop a base in the national economy where the implementation is carried out on the basis of democracy with the foundations of the principles of togetherness and justice which will later encourage harmony in the implementation of the economy in a sustainable and independent manner so as to form a company in the form of a PT which has competitive power as a driving force for increasing National PDP to provide welfare for all components. Legal consequences when a Money Laundering Crime occurs against a beneficial owner based on the Company Law and Presidential Regulation Number 13 of 2018 concerning the Application of the Principle of Beneficial Owners of Corporations in the Context of Prevention and Eradication of Money Laundering Crimes and Terrorism Financing Crimes, the beneficial owner must be submitted because the beneficial owner is not present in a limited liability company, the beneficial owner as a legal subject to influence or control the limited liability company without having to obtain authorization from any party and is the actual owner of the funds for the ownership of limited liability company shares based on the provisions of Article 4 paragraph (1) letters (e) and (g) so that the criminal act of money laundering and terrorism in a limited liability company is what is being pursued is the actor who is suspected of entering funds as a form of act of money laundering and terrorism.